Bone Mineral Density in Antiretroviral Therapy‐Naïve HIV‐1–Infected Young Adult ‐Women Using Depot Medroxyprogesterone Acetate or Nonhormonal Contraceptives in Uganda. (21st December 2020) - Matovu, Flavia Kiweewa; Nabwana, Martin; Kiwanuka, Noah; Scholes, Delia; Isingel, Esther; Nolan, Monica L; Fowler, Mary G; Musoke, Philippa; Pettifor, John M; Brown, Todd T; Beksinska, Mags E; ,
ABSTRACT: Most studies evaluating BMD in human immunodeficiency virus (HIV)‐infected populations have focused on antiretroviral therapy (ART)‐experienced patients. In this study, the association between HIV‐1 and/or depot medroxyprogesterone acetate (DMPA) and BMD among untreated HIV‐1–infected women in a resource‐limited setting was assessed before long‐term exposure to ART. The data were then compared with that of the 2005–2008 United States National Health and Nutrition Examination Survey data for non‐Hispanic White and Black women. Women aged 18–35 years, recruited from health facilities in Kampala, Uganda, were classified based on their combination of HIV‐1 status and DMPA use: (i) HIV‐1–infected current DMPA users, (ii) HIV‐1–infected previous DMPA users, (iii) HIV‐1–infected nonhormonal‐contraceptive users, and (iv) HIV‐uninfected nonhormonal‐contraceptive users. All HIV‐1–infected women reported being ART‐naïve at baseline. BMD was measured at the lumbar spine, total hip, and femoral neck using DXA. Multivariate linear regression was used to assess the association between HIV‐1 and/or DMPA and BMD Z ‐scores. Baseline data were analyzed for 452 HIV‐1–infected (220 nonhormonal users, and 177 current and 55 previous DMPA users) and 69 HIV‐1–uninfected nonhormonal‐contraceptive users. The mean age was 26.1 years (SD, 4.2) with a median duration of DMPA use among current users of 24.0 months [medians (interquartile range), 12‐48]. A higher proportion of HIV‐1–infected previous (12.7%) or current DMPA users (20.3%) and nonhormonal users (15.0%) had low BMD ( Z ‐score ≤−2 at any of the three sites) compared with age‐matched HIV‐1–uninfected women (2.9%). HIV‐1 infection and DMPA use were independently associated with significantly lower mean BMD Z ‐scores at all sites, with the greatest difference being among HIV‐1–infected current DMPA users (5.6%–8.0%) versus uninfected nonhormonal users. Compared with non‐Hispanic White and Black women, the Ugandan local reference population had generally lower mean BMD at all sites. Newer treatment interventions are needed to mitigate BMD loss in HIV‐1–infected women in resource‐limited settings. © 2020 The Authors. JBMR Plus published by Wiley Periodicals LLC. on behalf of American Society for Bone and Mineral Research.